Group Cohesiveness in Sidoarjo Manganese Community Volunteers - Endariyantono Endariyantono; Effy Wardati Maryam (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to identify and provide an explanation of the description of group cohesiveness in the Sidoarjo mangan community. This research method is descriptive quantitative with the subject of volunteer members in the Sidoarjo mangan community, totaling 138 people. Determination of the subject using a saturated sampling technique. Saturated sampling technique is a sampling technique when all members of the population are used. The variable in this study is group cohesiveness. The data collection in this study used a psychological preparation scale, namely the Likert scale for the group cohesiveness variable made by the researcher. Analysis of the data in this study using the help of SPSS 18.0 forum windows and Microsoft Excel. The results of data analysis showed that volunteer members of the Sidoarjo mangan community had group cohesiveness in the medium category with a percentage value of 70.3%, which means that volunteer members were able to bring about group cohesiveness when they were in the Sidoarjo mangan community.